Stackelberg game analysis of government subsidy on sustainable off-site construction and low-carbon logistics - Wen Yi; Lu Zhen; Yong Jin (Cleaner Logistics and Supply Chain)
This paper considers promoting off-site construction using government subsidy. A three-stage Stackelberg game model is formulated for the optimal subsidy design for the government, accounting for the decisions of government, suppliers (owners of off-site construction yards), and customers (entities that buy precast concrete from the suppliers). The government has two objectives: one is to maximize the use of precast concrete produced by regional yards and the other is to reduce green-house gas emissions from the transport of precast concrete. A number of properties of the three-stage Stackelberg game framework have been analyzed. We find that an inappropriately designed subsidy scheme may decrease the use of precast concrete produced by regional yards and increase green-house gas emissions from the transport of precast concrete, compared with a no-subsidy benchmark.